Erosion resistance in metal - ceramic multilayer coatings for gas turbine compressor applications - Goat, Christopher (Cranfield University, 1995)
The erosion resistance of 50 m metal-ceramic multilayer coatings has been investigated under impact conditions comparable to those in a gas turbine compressor cascade. lt was possible to improve upon the erosion resistance of Ti-6Al-4V by a significant margin. The influence of layer mechanical properties, layer thickness, ceramic content and coating process on erosion resistance has been studied over a range of impact conditions. The most suitable coating formulation for maximum erosion resistance changed with particle impact energy. Under low energy impact conditions (<55 joules) coatings with a high ceramic content demonstrated the highest erosion resistance. As particle impact energy increased, coatings with a high ceramic content perfonned poorly, and those containing a high volume fraction (50%) ductile metal layer, with thin metal and ceramic layers become more successful. Three principal damage types were observed: lateral fracture, tensile fracture and plastic definition. The most severe coating losses resulted from spallation due to lateral fracture. Coatings containing a high proportion of ductile metal with thin metal and ceramic layers were successful because such coatings had a high resistance to lateral fracture. Erosion resistance was greatest when the metal layer had a high yield strength and elastic modulus; such a combination of properties also resisted plastic definition. Scratch testing was investigated as a simple alterative technique for assessing coating erosion resistance. Repeated pass scratch testing generated similar damage modes to those of particle impact, but there was poor correlation between coating erosion rate and the threshold load for scratch damage.